"Mr. Cobb Knows Nothing About Architecture": Committee Assignment Requests in the Pre-Civil War US House of Representatives. Issue 2 (3rd May 2020) - Peart, Daniel
Abstract: Using letters addressed to two Speakers—James K. Polk (TN), 24th–25th Congresses, and Nathaniel P. Banks (MA), 34th Congress— this article examines committee assignment requests in the pre-Civil War House of Representatives. It begins by outlining the circumstances which concentrated enormous power over assignments in the hands of the Speaker. It then draws on existing literature on the modern House to propose several hypotheses, before explaining the challenges of applying conventional research methods to the collection and study of nineteenth-century data. That data is then analyzed to calculate the success rate of requests, rank committees by their attractiveness, and categorize the motives which drove members to seek a particular assignment. The article finds certain basic continuities with the modern House in these three aspects of the committee allocation process, and suggests explanations for the most striking discontinuities.